SYMMETRIC METHODS IN MATHEMATICAL PHYSICS - Сєров, Микола Іванович; Сєрова, Марія Михайлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Some directions of researches are resulted in industry of symmetric analysis of differential equalizations, which are conducted by the group of research workers of department of higher mathematics of the Poltava National Technical University by Yu. Kondratiuk. Procedure of nonlinear superposition of decisions is offered, which allows to build the chainless of decisions of type of onesolitonnih for equalizations sine-Gordon. Communication of some known and got decisions with the statements of conditional symmetry of equalization is explored sine-Gordon, which the classes of exact decisions of the given equalization are built by. It is found statements of conditional symmetry and classes of decisions for multidimensional wave equation proper to them sine-Gordon.